1994
DOI: 10.2214/ajr.163.2.8037042
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of intracranial lymphoma in patients with AIDS: value of 201TI single-photon emission computed tomography.

Abstract: OBJECTIVE.Although

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…Single-photon-emission computed tomography imaging using thallium-201 as the tracer in patients with PML has been reported, but the results were inconsistent (82,83).…”
Section: Neuroimaging In Pmlmentioning
confidence: 99%
“…Single-photon-emission computed tomography imaging using thallium-201 as the tracer in patients with PML has been reported, but the results were inconsistent (82,83).…”
Section: Neuroimaging In Pmlmentioning
confidence: 99%
“…Several studies have evaluated the utility of thallium-201 SPECT in distinguishing cerebral lymphoma from toxoplasmic encephalitis in patients with AIDS (table 5) [119,[133][134][135][136][137][138][139][140][141][142][143][144]. Although initial studies of thallium-201 SPECT showed a high sensitivity and specificity for the diagnosis of CNS lymphoma in patients with AIDS [133,134], subsequent reports reported lower diagnostic accuracy.…”
Section: Thallium-201 Single-photon Emission Ct (Spect)mentioning
confidence: 99%
“…Although initial studies of thallium-201 SPECT showed a high sensitivity and specificity for the diagnosis of CNS lymphoma in patients with AIDS [133,134], subsequent reports reported lower diagnostic accuracy. A compilation of the published studies revealed a mean sensitivity and specificity of 92% and 89%, respectively [119, 135-139, 141, 144-147].…”
Section: Thallium-201 Single-photon Emission Ct (Spect)mentioning
confidence: 99%
“…In this test, focal uptake of thallium in the region of the CNS lesion is characteristic of a neoplastic process, whereas absence of uptake in the area of the lesion is suggestive of a nonneoplastic process, such as an abscess. In one study of 13 AIDS patients with intracranial masses, thallium-201 SPECT was able to correctly rule out lymphoma in all six patients with studies showing no focal uptake [36]. Of the seven subjects with "positive" tests, six were proven to have lymphoma while one was found to have an infectious process (toxoplasmosis and cytomegalovirus).…”
Section: Imagingmentioning
confidence: 98%